What is Minsky all about, anyway? - Korkut Ertürk; Gökcer Özgür (The University of Utah, Department of Economics, 2009)
In this paper our objective is to sketch out an alternative understanding of Minsky as an evolving research agenda.At the most general level we hold that a Minksyan way of looking at the world boils down to few basic propositions: (i) in a financial capitalist economy, credit is procyclical in the absence of policies/institutions that actively neutralize it, and, that, in turn (ii) causes systemic risk to rise endogenously over an expansion (iii) in a way agents fail to recognize, (iv) and has the potential to blow up badly, ending in debt deflation. Defined thus, there is little question that the current financial crisis is a quintessential Minsky moment. If nothing else, the very fact that credit supply has become much more procyclical following financial deregulation has vindicated Minskys basic insight. Who can now in hindsight deny that financial liberalization played an important role in both stoking the speculative boom as well as the difficulty of containing deleveraging after the crisis?
Keywords: 330; Finanzmarktkrise; Kapitalmarktregulierung; Kapitalmobilität; Börsenkurs; Bubbles; Wissenschaftliche Methode